The connection of an old geodetic datum with a new one using Least Squares Collocation: The Greek case - AMPATZIDIS, Dimitrios; MELACHROINOS, Stavros (Contributions to Geophysics and Geodesy, 2017)
In the present paper we are dealing with the problem of the connection of two local geodetic datums in which the classical transformation procedures fail to give sufficient solution. Thereafter, we additionally implemented Least Squares Collocation in order to model the remaining residuals of the initial transformation. We tested this methodology in an area located in Northern Greece and we found significant improvement of the transformation results. The implementation of Least Squares Collocation refines the statistical behaviour of the inconsistencies regarding their extreme values (minimum and maximum) from almost 70 to 23 cm, while the standard deviation is reduced from the level of 27 to 10 cm.